Albert Henry Walker correspondence - Walker, Albert Henry, 1844-1915.
Chiefly letters to Walker relating to legal cases. Correspondents include Albert Jeremiah Beveridge, Samuel Gompers, Robert Green Ingersoll, Henry Cabot Lodge, Horace H. Lurton, Wayne MacVeagh, J. McKenna, and Knute Nelson.
In part, typewritten transcript.
Lawyer of New York, N.Y.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Beveridge, Albert Jeremiah, -- 1862-1927 -- Correspondence; Gompers, Samuel, -- 1850-1924 -- Correspondence; Ingersoll, Robert Green, -- 1833-1899 -- Correspondence; Lodge, Henry Cabot, -- 1850-1924 -- Correspondence; Lurton, Horace H. -- 1844-1914 -- Correspondence; MacVeagh, Wayne, -- 1833-1917 -- Correspondence; McKenna, J. -- 1843-1926 -- Correspondence; Nelson, Knute, -- 1843-1923 -- Correspondence; Practice of law -- New York (State) -- New York; Lawyers